2008
DOI: 10.1021/ja076568q
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Formation in Polythiophene/Fullerene Blend Films Studied by Transient Absorption Spectroscopy

Abstract: Abstract:We report herein a comparison of the photophysics of a series of polythiophenes with ionization potentials ranging from 4.8 to 5.6 eV as pristine films and when blended with 5 wt% 1-(3-methoxycarbonyl)propyl-1-phenyl-[6,6]C 61 (PCBM). Three polymers are observed to give amorphous films, attributed to a non-planar geometry of their backbone whilst the other five polymers, including poly(3-hexylthiophene), give more crystalline films. Optical excitation of the pristine films of the amorphous polymers is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
768
5
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 634 publications
(837 citation statements)
references
References 92 publications
61
768
5
3
Order By: Relevance
“…Based on this observation, they proposed that the excess energy after the exciton dissociation provide extra kinetic energy for the CT state dissociation. 67 This hot CT state theory was further supported by their subsequent work on other polymer:fullerene blends as well as polymer:perylene diimide blends ( Figure 6). [69][70][71][72][73][74] In addition to the above work, there are some other reports supporting the hot CT state theory.…”
Section: Dissociation Via the Hot Ct Statementioning
confidence: 69%
See 2 more Smart Citations
“…Based on this observation, they proposed that the excess energy after the exciton dissociation provide extra kinetic energy for the CT state dissociation. 67 This hot CT state theory was further supported by their subsequent work on other polymer:fullerene blends as well as polymer:perylene diimide blends ( Figure 6). [69][70][71][72][73][74] In addition to the above work, there are some other reports supporting the hot CT state theory.…”
Section: Dissociation Via the Hot Ct Statementioning
confidence: 69%
“…67 The authors found that the yield of the dissociated polarons varied by two orders depending on polythiophenes used, in spite of efficient PL quenching for all the blends. They observed a strong dependence of the yield of dissociated polarons on the energy difference between the singlet exciton and the dissociated polarons.…”
Section: Dissociation Via the Hot Ct Statementioning
confidence: 99%
See 1 more Smart Citation
“…64 This requirement comes from the relatively low dielectric constant of such organic materials, resulting in relatively strong coulomb attraction of electrons and holes and causing geminate recombination losses to become a significant loss pathway in such devices. This situation can be contrasted with the electron injection dynamics we report here for DSSCs.…”
Section: Correlation Between Injection Kinetics and Device Performancementioning
confidence: 99%
“…A possibly more favorable free energy of charge generation through improved band alignment for ordered P3HT chains remains to be investigated. 56 Recent results state a rise only of the HOMO energy level and no change of the LUMO level through chain ordering. 57 For a possible photovoltaic application, we compared RR-P3HT:Si-ncs BHJs with aggRR-P3HT/poly-Si PHJs.…”
Section: Articlementioning
confidence: 99%